Anaerobic Soccer Training Model: Enhancing Soccer Players’ Performance through a Combination of Repeated Sprints and 4 vs 4 Games - Kusuma, I Dewa Made Aryananda Wijaya; Kusnanik, Nining Widyah; Pramono, Bayu Agung; Pranoto, Adi; Phanpheng, Yanyong; Susanto, Indra Himawan; Amustikarani, Dewa Ayu Praba; Nirwansyah, Waristra Tyo; Bharlaman, Muhammad Bagus Firzam (Physical Education Theory and Methodology, 2025)
Objectives. The Anaerobic Soccer Training (AnST) model was designed to increase variation in soccer training programs by implementing a game-based approach to matching characteristics. This study aimed to evaluate the effectiveness of the training model in improving soccer players’ anaerobic abilities. Materials and methods. The research method used was the ADDIE model consisting of five integrated phases: Analysis, Design, Development, Implementation, and Evaluation. Eighty-two soccer players from the UNESA male student activity unit were involved in this study, with 20 samples taken using random sampling techniques. Sample characteristics included the following data: age 20.05 ± 0.69 years, height 165.85 ± 5.00 cm, weight 62.08 ± 6.82 kg, and BMI 22.54 ± 1.98. The intervention was carried out over a four-week period, with a frequency of three times a week. The Aiken’s V test was used to analyze the assessment data from three expert judgments, followed by percentage analysis for content validity. The normality test was conducted using the Shapiro-Wilk test, while the mean difference was analyzed using the paired sample t-test. Results. The results showed that in variables for peak power (.001), mean power (.000), fatigue index (.013), Lactate Week (LW) 1-2 (.020) and LW1-3 (.038), notable differences with significance values ​​below 0.05 were observed. In contrast, LW1-4 (.631) did not demonstrate significant differences. Overall, the development of the AnST model successfully improved the anaerobic ability of players, as evidenced by an increase in peak power, mean power, and a decrease in the fatigue index. Conclusions. These findings indicate that this training model is effective in enhancing the anaerobic performance in soccer players.